Peralihan Hak Atas Tanah Di Desa Bumi Kencana Kecamatan Sungai Lilin Kabupaten Musi Banyuasin - Marsall Aqila, Rifda; Rosmidah, Rosmidah (Zaaken: Journal of Civil and Business Law, 2023)
The purpose of this study was to find out and analyze the implementation of the transfer of land rights, constraints, and legal consequences of the transfer of land rights in Bumi Kencana Village, Sungai Lilin District, Musi Banyuasin Regency. This research is an empirical juridical research using primary data and secondary data as well as qualitative analysis. The results of the study show that the transfer of land rights in Bumi Kencana Village is generally carried out by way of buying and selling and grants according to custom and it is recognized that the transfer of land rights is only carried out before the Village Head, Neighboring Units, Sellers and Buyers, and Boundary Witnesses. Tanah Bumi Kencana Kec. Sungai Lilin Kab. Musi Banyuasin has a land area of 25,043,978 Ha, while those with certificates are 12,125,000 Ha. The people of Bumi Kencana Village usually make customary transitions because it has become commonplace among the community, in general, transferring land rights in a customary way is only legal in adat, but not legal because there is no legal certainty. Â